Magnetism of the 35 K superconductor CsEuFe4As4. (21st March 2018) - Albedah, Mohammed A; Nejadsattari, Farshad; Stadnik, Zbigniew M; Liu, Yi; Cao, Guang-Han
Abstract: The results of ab initio hyperfine-interaction parameters calculations, and of x-ray diffraction and 57 Fe and 151 Eu Mössbauer spectroscopy study of the new 35 K superconductor CsEuFe4 As4 are reported. The superconductor crystallizes in the tetragonal space group P 4/ mmm with the lattice parameters a = 3.8956 ( 1 ) Å and c = 13.6628 ( 5 ) Å. It is demonstrated unequivocally that there is no magnetic order of the Fe magnetic moments down to 2.1 K and that the ferromagnetic order is associated with the Eu magnetic moments. The Curie temperature T C = 15.97 ( 8 ) K determined from the temperature dependence of the hyperfine magnetic field at 151 Eu nuclei is shown to be compatible with the temperature dependence of the transferred hyperfine magnetic field at 57 Fe nuclei that is induced by the ferromagnetically ordered Eu sublattice. The Eu magnetic moments are shown to be perpendicular to the crystallographic c -axis. The temperature dependence of the principal component of the electric field gradient tensor, both at Fe and Eu sites, is well described by a T 3/2 power-law relation. Good agreement between the calculated and measured hyperfine-interaction parameters is observed. The Debye temperature of CsEuFe4 As4 is found to be 295(3) K.